1993
DOI: 10.1136/gut.34.5.665
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal epithelial cells contribute to the enhanced generation of platelet activating factor in ulcerative colitis.

Abstract: Generation of platelet activating factor by intestinal mucosal epithelial cells and lamina propria mononuclear cells was evaluated to elucidate the possible role of this mediator in the pathogenesis of inflammatory bowel disease. Epithelial and lamina propria mononuclear cells were isolated from surgical specimens from control, Crohn's disease, and ulcerative colitis patients. Platelet activating factor was extracted from highly purified cell preparations with 80% ethanol after stimulation with and without 0*2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…These indicated that PAF might be involved in the pathogenesis of Crohn's disease [142] . The elevated level of PAF in colon was likely to be the result of increased production by colonic epithelial cells [143] , lamina propria mononuclear cells [144] and mast cells, and decreased PAF acetylhydrolase (the major PAF degradation enzyme activity) [145] . In patients with ulcerative colitis, colonic production of PAF was increased in comparison with control patients [146] , and the level of PAF in the stool of patients with ulcerative colitis was much higher than that in the stool of healthy volunteers [147] .…”
Section: Involvement Of Pgd2 Ltc4 and Paf In Pathogenesis Of Ibdmentioning
confidence: 99%
“…These indicated that PAF might be involved in the pathogenesis of Crohn's disease [142] . The elevated level of PAF in colon was likely to be the result of increased production by colonic epithelial cells [143] , lamina propria mononuclear cells [144] and mast cells, and decreased PAF acetylhydrolase (the major PAF degradation enzyme activity) [145] . In patients with ulcerative colitis, colonic production of PAF was increased in comparison with control patients [146] , and the level of PAF in the stool of patients with ulcerative colitis was much higher than that in the stool of healthy volunteers [147] .…”
Section: Involvement Of Pgd2 Ltc4 and Paf In Pathogenesis Of Ibdmentioning
confidence: 99%
“…These cells present antigens via class II molecule expression (Mayer et al, 1991;Lowes et al, 1992), express adhesion proteins such as intracellular adhesion molecule-i (Kaiserlian et al, 1991) and generate soluble inflammatory mediators e.g. arachidonic acid derivatives (Gustafson & Tagesson, 1990;Dias et al, 1992), platelet activating factor (Ferraris et al, 1993), and cytokines (Spriggs et al, 1988;Hedges et al, 1992;Eckmann et al, 1993;Schuerer-Maly et al, 1994;Gross et al, 1995), all of which contribute to the communication between inflammatory cells and cells of the immune system (Sartor, 1994). Several proinflammatory mediators such as interleukin-1 (IL-1), interleukin-6 (IL-6), leukotrienes, tumour necrosis factor-a (TNF-a), prostaglandins, and complement are increased in actively inflamed colonic tissues from patients with inflammatory bowel disease (Lichtman & Sartor, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…PAF is produced by intestinal epithelial cells 24 and these cells express PAF-receptors. 36 PAF has been found to have potent chemotactic properties on neutrophils via the production of endogenous leukotriene B4.…”
Section: Cxcl2 C C Lps Ctrol Abmentioning
confidence: 99%
“…21 Other investigators have found that LPS stimulates intestinal epithelial cells to produce TNF 22,23 and PAF. 24 Thus, it is possible that LPS may directly stimulate enterocytes to express CXCL2 via the activation of NFjB, and this effect may be mediated via endogenous production of TNF and PAF.…”
mentioning
confidence: 99%